2011
DOI: 10.1007/s00404-011-2093-5
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal hysterectomy and multimodal anaesthesia with bipolar vessel sailing (Biclamp® forceps) versus conventional suture technique: quality results’ analysis

Abstract: BiClamp(®) technique with multimodal anaesthesia has advantages from surgical, anaesthesiology and economic point of view. It is a minimally invasive surgery characterised by lower morbidity, quicker surgery times and reduced costs when compared to classical vaginal hysterectomy. BiClamp(®) technique represents a new border in vaginal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…L'utilisation de la thermofusion a prouvé son bénéfice sur les sutures classiques dans les hystérectomies en terme de diminution des saignements [46,47] et de réduction du temps opératoire [46,48,49]. L'utilisation de la thermofusion a aussi permis de diminuer de façon significative la durée du séjour hospitalier après hystérectomie vaginale et annexectomie bilatérale [50] mais aussi après hystérectomie par laparotomie [51]. Devant un désir de prise en charge en ambulatoire, ces outils semblent indispensables puisqu'ils permettent de diminuer le temps opératoire, les saignements peropératoires et les douleurs postopératoires [52,53].…”
Section: Critères Post-opératoiresunclassified
“…L'utilisation de la thermofusion a prouvé son bénéfice sur les sutures classiques dans les hystérectomies en terme de diminution des saignements [46,47] et de réduction du temps opératoire [46,48,49]. L'utilisation de la thermofusion a aussi permis de diminuer de façon significative la durée du séjour hospitalier après hystérectomie vaginale et annexectomie bilatérale [50] mais aussi après hystérectomie par laparotomie [51]. Devant un désir de prise en charge en ambulatoire, ces outils semblent indispensables puisqu'ils permettent de diminuer le temps opératoire, les saignements peropératoires et les douleurs postopératoires [52,53].…”
Section: Critères Post-opératoiresunclassified
“…Of these, 39 were excluded because they did not meet eligibility criteria. Thus, 116 studies were included in the final analysis, 11,23–137 including 15 RCTs, 17 nonrandomized comparative studies, and 84 single-group studies (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies examined the use of a tissue sealing, stapling, or suturing device compared with traditional clamping and suture ligation during vagi-nal hysterectomy (n51,389). The number of study participants per trial ranged from 10 36 to 200, 37 and study qualities were good, [38][39][40][41][42][43] fair, 44,45 and 12,13,16,18 Bilateral salpingooophorectomy 1 Insufficient evidence is available to comment on factors associated with successful completion of BSO 59 Peritoneal closure 5 Five studies evaluated peritoneal closure (n5363) with fair [60][61][62][63] and poor 64 study quality; three studies compared only closing peritoneum with only closing vaginal epithelium (n5207) 60,62,64 ; overall, no difference was seen in complications between groups with the exception of one study that intentionally left a small portion of the peritoneum open to drain, which reported one fallopian tube prolapse and one bowel evisceration 62 ; all of these studies were underpowered for both their primary and secondary outcomes; there is insufficient evidence to recommend for or against adding peritoneal closure when closing the vaginal cuff Tissue sealers 2 One study evaluated the Multifire Endo-GIA stapler compared with traditional suture ligation (n510) 46 ; another study compared an aneurysm needle suture technique with traditional suturing (n546) 37 ; based on the limited data regarding these techniques, reliable conclusions cannot be made…”
Section: Postoperativementioning
confidence: 99%
“…36,37,[46][47][48][49][50] Eight studies evaluated the Ligasure, 36,[38][39][40]43,44,48,50 and four examined other similar bipolar clamps. 42,45,47,49 One study evaluated ultrasonic shears compared with traditional suture ligation (n543). 41 Narcotic analgesia use, length of hospital stay, hysterectomy time, and total operative time were similar in both groups (high strength of evidence).…”
Section: Bladder Functionmentioning
confidence: 99%